(untitled) (The International Research Journal of Management Science, 2018)
Training culture is the aggregate of meaning, values, practices, attitude and behavior as to invest in training and development so that organizational knowledge and skills could be enhanced. Advanced knowledge, capabilities and skills are proved to be source of competitive advantage of the organization as these assets hold dominant role in customer’s satisfaction and retention. Organizations have two choices as to acquire competent employees from the industry or to build their competencies. The second choice becomes more appropriate from organizational image, employee satisfaction and retention along with the improved performance. Organizations, thus, need to establish a training culture for sustainable growth of organization. It could be the only way to reduce the cost of hiring competent employees and reducing the cost of losing competent employees. Performance of the employees can be sustained with training. This study aims to examine whether Nepali banking sector has established training culture? If yes, whether training has significant influence in performance? This study follows descriptive and correlational research design. Structured questionnaire with 5-point Likert scale is used to collect the information. Mean, standard deviation, correlation and independent sample t-test are used to analyze the data. Result revealed that Nepali banks have established the training culture. Training environment, training methods, training-reward linkage are the major factors of training culture affecting training satisfaction and employee performance. Employees are satisfied through the skills acquired from training. Gender and the bank types have mediating role in training satisfaction and employee performance.